1998
DOI: 10.1002/(sici)1097-4628(19980613)68:11<1883::aid-app21>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Grafting reaction of living polymer cations with amino groups on chitosan powder

Abstract: ABSTRACT:The grafting of polymers having controlled molecular weight and narrow molecular weight distribution onto chitosan powder by the termination of living polymer cation with amino groups on chitosan powder was investigated in heterogeneous system. The amino groups of chitosan powder successfully reacted with living poly(isobutyl vinyl ether) [poly(IBVE)] and poly(2-methyl-2-oxazoline) [poly(MeOZO)] cation with controlled molecular weight and narrow molecular weight distribution to give the corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Some years ago, Yoshikawa et al showed that grafting reactions onto chitosan can also be performed by using living cationic polymerization [49]. These authors grafted chitosan with living poly(isobutylvinyl ether) and poly(2-methyl-2-oxazoline) cation with controlled molecular weight distribution.…”
Section: Cationic Graft Polymerizationmentioning
confidence: 99%
“…Some years ago, Yoshikawa et al showed that grafting reactions onto chitosan can also be performed by using living cationic polymerization [49]. These authors grafted chitosan with living poly(isobutylvinyl ether) and poly(2-methyl-2-oxazoline) cation with controlled molecular weight distribution.…”
Section: Cationic Graft Polymerizationmentioning
confidence: 99%
“…TGA measurements also confirmed that grafting poly(PEGMA‐ co ‐S) to CTS via grafting from improved the thermal stability compared to CTS ‐g‐ GMA‐poly(PEGMA‐ co ‐S) obtained via a grafting to approach. This unexpected improvement in the thermal stability may be attributed to the higher graft density achieved with the grafting from approach, or some termination of the growing chains leading to cross‐linking, as it has been previously observed …”
Section: Resultsmentioning
confidence: 51%
“…Short reaction times were used as the polymerization of methacrylate monomers is considerably faster than styrenic or acrylic monomers. It has been established that in grafting from polymerizations, low initiation efficiency is a common issue, and, therefore, it was decided to use a large excess of monomers to promote the grafting reaction …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grafting of chitosan with living poly(isobutylvinyl ether) and poly(2-methyl-2-oxazoline) cations with controlled molecular weight distribution has been reported [124]. In this study, researchers have analyzed the effect of the molecular weight of living polymer cations on the number of grafted polymers; it was found that the number of grafted polymer chains decreased with the increasing molecular weight of living polymer cations.…”
Section: Cationic Graft Polymerizationmentioning
confidence: 99%